Canakinumab in patients with COVID-19 and type 2 diabetes – A multicentre, randomised, double-blind, placebo-controlled trial. (November 2022) - Hepprich, Matthias; Mudry, Jonathan M.; Gregoriano, Claudia; Jornayvaz, Francois R.; Carballo, Sebastian; Wojtusciszyn, Anne; Bart, Pierre-Alexandre; Chiche, Jean-Daniel; Fischli, Stefan; Baumgartner, Thomas; Cavelti-Weder, Claudia; Braun, Dominique L.; et al.
Summary: Background: Patients with type 2 diabetes and obesity have chronic activation of the innate immune system possibly contributing to the higher risk of hyperinflammatory response to SARS-CoV2 and severe COVID-19 observed in this population. We tested whether interleukin-1β (IL-1β) blockade using canakinumab improves clinical outcome. Methods: CanCovDia was a multicenter, randomised, double-blind, placebo-controlled trial to assess the efficacy of canakinumab plus standard-of-care compared with placebo plus standard-of-care in patients with type 2 diabetes and a BMI > 25 kg/m 2 hospitalised with SARS-CoV2 infection in seven tertiary-hospitals in Switzerland. Patients were randomly assigned 1:1 to a single intravenous dose of canakinumab (body weight adapted dose of 450-750 mg) or placebo. Canakinumab and placebo were compared based on an unmatched win-ratio approach based on length of survival, ventilation, ICU stay and hospitalization at day 29. This study is registered with ClinicalTrials.gov, NCT04510493. Findings: Between October 17, 2020, and May 12, 2021, 116 patients were randomly assigned with 58 in each group. One participant dropped out in each group for the primary analysis. At the time of randomization, 85 patients (74·6 %) were treated with dexamethasone. The win-ratio of canakinumab vs placebo was 1·08 (95 % CI 0·69-1·69; p = 0·72). During four weeks, in the canakinumab vs placebo group 4 (7·0%) vs 7 (12·3%) participants died, 11 (20·0 %) vs 16 (28·1%) patients were on ICU, 12 (23·5 %) vs 11 (21·6%) were hospitalised for more than 3 weeks, respectively. Median ventilation time at four weeks in the canakinumab vs placebo group was 10 [IQR 6.0, 16.5] and 16 days [IQR 14.0, 23.0], respectively. There was no statistically significant difference in HbA1c after four weeks despite a lower number of anti-diabetes drug administered in patients treated with canakinumab. Finally, high-sensitive CRP and IL-6 was lowered by canakinumab. Serious adverse events were reported in 13 patients (11·4%) in each group. Interpretation: In patients with type 2 diabetes who were hospitalised with COVID-19, treatment with canakinumab in addition to standard-of-care did not result in a statistically significant improvement of the primary composite outcome. Patients treated with canakinumab required significantly less anti-diabetes drugs to achieve similar glycaemic control. Canakinumab was associated with a prolonged reduction of systemic inflammation. Funding: Swiss National Science Foundation grant #198415 and University of Basel. Novartis supplied study medication.